Transarterial Chemoembolization Combined With Hepatectomy for the Treatment of Intermediate-Stage Hepatocellular Carcinoma - Zhou, Qunfang; Tuo, Fei; Li, Ruixia; Wang, Xiaohui; Wang, Juncheng; Huang, Zhimei; Chen, Minshan; Huang, Jinhua (Frontiers in Oncology, 2020)
Background: Transarterial chemoembolization (TACE) is currently the recommended treatment for intermediate-stage hepatocellular carcinoma (HCC). Liver resection (LR) may be an effective option, though recurrences are not uncommon. TACE prior to LR has been proposed as an even better alternative. Methods: Patients with intermediate-stage HCC who underwent curative resection were enrolled between January 2007 and December 2015. We compared overall survival (OS) and recurrence-free survival (RFS) for the 2 groups using the Kaplan-Meier method, and we determined independent risk factors for death and recurrence using multivariate regression analyses. Results: A total of 488 patients with HCC at BCLC B (265 patients with LR, 223 patients with TACE+LR) enrolled from our center. Mean follow-up was 40.2 (range, 3.0-128.7) months. For patients receiving TACE+LR and LR, estimated 1-, 3-, and 5-year OS rates were 90.6% and 73.3%, 61.7% and 43.5%, and 52.9% and 33.8%, respectively (all P < 0.001) and estimated 1-, 2-, and 3-year RFS rates were 54.6% and 39.4%, 41.4% and 29.4%, and 36.3% and 26.3%, respectively (P < 0.001, P = 0.002, and P = 0.008, respectively). Significant independent predictors of poor OS were more than 3 (vs. 3 or fewer) tumors (HR=2.19, 95% CI 1.69-2.84), non-anatomical (vs. anatomical) hepatectomy (HR=1.29, 95% CI 1.01-1.66), microscopic vascular invasion (HR=1.46, 95% CI 1.15-1.90), cirrhosis (HR=2.41, 95%CI 1.88-3.01), and intraoperative blood transfusion (HR=1.29, 95% CI 1.01-1.66). Conclusion: Preoperative TACE with LR may result in better oncological outcomes than either TACE or LR alone, without a substantial increase in morbidity, and could be considered an effective combination treatment for intermediate-stage HCC.